Epidemiology of snake bites in selected areas of Kenya - Ochola, Francis Okumu (Pan Afr Med J, 2018)
INTRODUCTION: Snake bites are a silent public health problem in Kenya. Previous studies on snake bites in the country have mainly focused on identifying offending snake species, assessing the severity of envenomation and testing the efficacy of antivenom. Factors associated with snake bites in the country are yet to be fully understood. The aim of this work was to determine pharmaco-epidemiological factors associated with snake bites in areas of Kenya where incidence, severity and species responsible for snake bites have been reported. METHODS: Kakamega provincial hospital, Kabarnet, Kapenguria and, Makueni district hospitals were selected as study sites based on previous findings on incidence, severity and species responsible for snake bites in catchment areas of these hospitals. Persistent newspaper reports of snake bites in these areas and distribution of snakes in Kenya were also considered. Cases of snake bites reported between 2007-2009 were retrospectively reviewed and data on incidence, age, site of the bites, time of bite and antivenom use was collected. RESULTS: 176 bites were captured, 91 of which occurred in 2009. Individual incidence was between 2.7/100,000/year and 6.7/100,000/year. Bites peaked in the 1-15 year age group while 132/176 bites were in the lower limb area and 49/176 victims received antivenom. Most bites occurred during the dry season, in the bush and in the evening. Overall mortality was 2.27%. CONCLUSION: There is a need to sensitize the Kenyan public and healthcare personnel on preventive measures, first aid and treatment of snake bites.